2004
DOI: 10.1088/0953-8984/16/21/004
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced structural phase transition in the IV–VI semiconductor SnS

Abstract: The structural behaviour of SnS under high-pressure has been investigated by angular dispersive synchrotron powder diffraction up to 38.5 GPa. A structural phase transition from orthorhombic α-SnS to monoclinic γ-SnS was observed at 18.15 GPa. The fit of a Birch–Murnaghan equation-of-state gave the volume at zero pressure of V0 = 192.6(3) Å3, the bulk modulus at zero pressure of B0 = 36.6(9) GPa and the pressure derivative of the bulk modulus for α-SnS and V0 = 160(1) Å, B0 = 86.0(5) GPa and for γ-SnS. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
67
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 40 publications
13
67
1
Order By: Relevance
“…The calculated lattice parameters are in good agreement with experimental data for bulk SnS (a=4.33Å, b=3.98Å and c= 11.20Å) [9,32] A, b=4.15Å, and c=11.50). [33] Our results are also in agreement with previous theoretical studies of SnS [11,14,34].…”
Section: A Crystal Structuresupporting
confidence: 82%
“…The calculated lattice parameters are in good agreement with experimental data for bulk SnS (a=4.33Å, b=3.98Å and c= 11.20Å) [9,32] A, b=4.15Å, and c=11.50). [33] Our results are also in agreement with previous theoretical studies of SnS [11,14,34].…”
Section: A Crystal Structuresupporting
confidence: 82%
“…The layers themselves because of the zig-zagging have finite thickness and along the 'b' axis have strong 'intra-planar' forces acting within them. Ehm [29] has shown that the application of pressure decreases inter-planar distances along 'b' axis without disturbing intra-planar spacing. As stated above, the Raman B 2g peak represents vibrations along the 'b' axis.…”
Section: Resultsmentioning
confidence: 99%
“…In x-ray diffraction experiments on SnS, Ehm et al observed an abrupt phase transition between 16 and 18 GPa [32]. A monoclinic lattice and space group P2 1 /c were tentatively assigned to the high-pressure phase, and on this basis a volume jump of ∆V/V ≈ −9% was inferred to occur at the transition.…”
Section: Comparison With Related Systemsmentioning
confidence: 99%